Bedrock geology, Ravn River, Baffin Island, Nunavut, NTS 37-G east 1:100,000 Map - Skipton, D R; Saumur, B M; St-Onge, M R; Wodicka, N; Bros, E R; Weller, O. M. (Natural Resources Canada, 2020)
This map presents the field observations and initial geological interpretations for the Ravn River area (NTS 37-G east) Baffin Island, Nunavut. The regional bedrock geology depicted on CGM maps 402 to 406 comprises Archean tonalitic to monzogranitic gneiss that includes mafic to intermediate components, and relatively homogeneous monzogranite-granodiorite intrusions. The Archean Mary River Group forms discontinuous volcano-sedimentary belts, consisting of mafic volcanic rocks interlayered with siliciclastic strata, banded iron-formation, and felsic to intermediate and ultramafic volcanic units. The supracrustal rocks are intruded by monzogranite-granodiorite plutons. Pelitic to psammitic units, marble, and calc-silicate of the middle Paleoproterozoic Piling Group unconformably overlie the Archean units. Archean units are also unconformably overlain by Mesoproterozoic clastic and carbonate platform sequences of the Bylot Supergroup. These strata were deposited within a graben that forms part of the larger Borden Basin. Paleozoic (Cambrian to Ordovician) strata lie unconformably upon Archean and Paleoproterozoic felsic plutonic rocks in the western portion of northern Baffin Island.